Legal Protection of Geographical Indications for Traditional Alcoholic Beverages: Perspectives of Islamic Law and Positive Law in Indonesia - Muhammad, Hasman Zhafiri; Ramadhan, Galih Dwi (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
Geographical indication is a form of legal protection for a sign identity of a product related to its region of origin. Various traditional alcoholic beverage products from abroad, such as 'tequila' from Mexico, 'whiskey' from Scotland and 'Pisco' from Peru, are examples of these foreign alcoholic drinks that have been protected by geographical indications in their countries of origin. This research aims to discuss Islamic views and positive law regarding Geographical Indications of alcoholic beverages in Indonesia. The method used is to use a normative method with a Qur'anic and juridical approach in studying alcoholic drinks in Islamic law with references from the Qur’an, and Hadith. The results of this research can be understood that the legal protection of traditional Indonesian alcoholic drinks as Geographical Indications presents significant challenges from an Islamic perspective. It is important for the government to find a middle way that can accommodate the interests of protecting local cultural and economic products, while still respecting religious values. [Abstrak Indikasi geografis merupakan sebuah bentuk perlindungan hukum terhadap tanda identitas suatu produk yang berkaitan dengan daerah asalnya. Berbagai produk minuman alkohol tradisional dari luar negeri seperti ‘tequila’ dari negara meksiko, ‘whisky’ dari negara Skolandia dan ‘Pisco’ dari negara Peru, dari contoh minuman alkohol luar negeri tersebut telah dilindungi oleh indikasi geografis di negara asalnya. Penelitian ini bertujuan untuk meneliti pandangan Islam dan hukum positif dalam hal Indikasi Geografis minuman beralkohol di Indonesia. Metode yang digunakan ialah menggunakan metode normatif dengan pendekatan Qur’ani dan Yuridis dalam mengkaji tentang minuman beralkohol dalam hukum Islam dengan refrensi dari Al-Quran dan Hadist. Hasil dari penelitian menunjukan dapat dipahami bahwa Perlindungan hukum terhadap minuman alkohol tradisional Indonesia sebagai Indikasi Geografis memberikan tantangan signifikan dalam perspektif Islam. Penting bagi pemerintah untuk mencari jalan tengah yang dapat mengakomodasi kepentingan perlindungan produk budaya dan ekonomi lokal, namun tetap menghormati nilai-nilai agama]